Enhanced photocatalytic performance of CdO-WO3 composite for hydrogen production. (20th September 2019) - Tahir, Muhammad Bilal; Sagir, Muhammad; Abas, Naeem
Abstract: Considering the renewability and cleanness of hydrogen generation system, the photocatalytic H2 evolution through water splitting with assistance of Earth abundant co-catalysts has become a scientific hotspot. Efficient and visible light driven CdO-WO3 composites with versatile properties have been fabricated through hydrothermal approach for H2 evolution. X-ray diffractometer, scanning electron microscope, UV-Vis absorption spectroscopy, photoluminescence emission spectroscopy and photocatalytic activity test were employed to investigate different properties like crystallography, morphology, optical and photocatalytic properties. The effect of CdO concentration on the grain size indicated the reduction of bad gap energy of the WO3 . The concentration of CdO nanoparticles in WO3 directly effect on the morphology of the particles that are in the form of nanorods. The atoms of CdO makes the WO3 nanoparticles more effective and efficient up to 4% of CdO but when coupling amount increases then the CdO-WO3 nanoparticles exhibited less photocatalytic performance to evolve H2 energy. Results shown that 4% content in WO3 had exceptional photocatalytic activity for water splitting when compared to other samples. The improved hydrogen production was allied with formation of active Cd species during the photocatalysis process, which has the ability to promote the interfacial charge-separation and concurrently may cause to reduce the over potential of hydrogen evolution, thus boosting the photocatalytic activity over the hybrid sample. The improved photocatalytic activity of composites could be accredited to extended absorption region of visible light, efficient separation of charge carrier's and suppress recombination of electron-hole pairs. The current work not only shows a prospect for the utilization of low cost CdO as a co-catalyst in photocatalytic hydrogen generation but also shows a substantial enhancement in H2 evolution, first time, using CdO-WO3 hybrid photocatalyst. Highlights: Successful synthesis of WO3 @ CdO photocatalysts by hydrothermal method. Extended visible-light absorption due to hybrid nanocomposites. Efficient charge-separation due to synergistic effects of CdO in WO3 photocatalyst. Enhanced photocatalytic activity for nanocomposites under visible-light irradiation.